Copper in hepatocellular carcinoma： A double-edged sword with therapeutic potentials - Wu, Zixin; Lv, Guishuai; Xing, Fuxue; Xiang, Wei; Ma, Yue; Feng, Qiyu; Yang, Wen; Wang, Hongyang (Cancer letters, 2023)
Copper is a necessary cofactor vital for maintaining biological functions, as well as participating in the development of cancer. A plethora of studies have demonstrated that copper is a double-edged sword, presenting both benefits and detriments to tumors. The liver is a metabolically active organ, and an imbalance of copper homeostasis can result in deleterious consequences to the liver. Hepatocellular carcinoma (HCC), the most common primary liver cancer, is a highly aggressive malignancy with limited viable therapeutic options. As research advances, the focus has shifted towards the relationships between copper and HCC. Innovatively, cuproplasia and cuproptosis have been proposed to depict copper-related cellular growth and death, providing new insights for HCC treatment. By summarizing the constantly elucidated molecular connections, this review discusses the mechanisms of copper in the pathogenesis, progression, and potential therapeutics of HCC. Additionally, we aim to tentatively provide a theoretical foundation and gospel for HCC patients. •The maintenance of copper homeostasis is essential for normal physiological functions.•Copper exhibits both promoting and inhibitory effects on the occurrence and development of liver cancer.•Cuproptosis holds broad application prospects in exploring new therapeutic targets and drug development for liver cancer.•Targeting cuproplasia by utilizing copper chelators and copper ion carriers could antagonize tumorigenesis.